Common Goods and the Civil Economy (Cultura Económica, 2018)
The article begins with the question about the problem of goods and property, and wonders which element of the conceptual infrastructure in economics must change so that a civil solution to the problem of the commons could be implemented. For this, the author develops the concepts of common good and civil economy. Then, the author describes the nature of commons and its management. Finally, Zamagni highlights the importance of promoting the implementation of community management practices of common goods.
Keywords: COMMON GOODS; PUBLIC GOODS; PRIVATE GOODS; EXCLUDABILITY; CIVIL ECONOMY